Experimental and computational investigation of the laminar burning velocity of hydrogen-enriched biogas. (1st January 2019) - Kumar Yadav, Vinod; Ray, Anjan; Ravi, M.R.
Abstract: Experimental investigation of the adiabatic laminar burning velocity (LBV) of mixtures representative of biogas and hydrogen-enriched biogas was carried out using heat flux method (HFM). To prepare samples of biogas for testing, pure methane (CH4 ) was diluted with 5–50 percent carbon dioxide (CO2 ). Thereafter, some of the biogas samples were enriched with either 20% or 40% hydrogen (H2 ). The combined effect of dilution with CO2 and enrichment with H2 on the LBV of CH4 at different equivalence ratios were studied experimentally using HFM and computationally using ANSYS Chemkin-Pro ® with GRI Mech. 3.0 and San Diego reaction mechanisms. The experimental results indicate that dilution with CO2 reduces the LBV of richer mixtures more significantly than that of leaner or stoichiometric mixtures. However, when the biogas samples were enriched with H2, a significant rise in the LBV was observed for fuels with higher content of CO2 . Sensitivity analyses of mass flow rate using GRI Mech. 3.0 revealed that with increased CO2 concentration, the sensitivity coefficient of H + O2 ↔ O + OH (R38) increases significantly and that of OH + CO ↔ H + CO2 (R99) decreases slightly. The sensitivity coefficients of H + O2 + H2 O ↔ HO2 + H2 O (R35) and H + CH3 (+M) ↔ CH4 (+M) (R52) are largest for fuel with the maximum percentage of CO2 . Further, with an increased H2 concentration in biogas mixtures, the sensitivity coefficient of H + O2 ↔ O + OH (R38) increases, and that of OH + CO ↔ H + CO2 (R99) decreases. Additionally, the sensitivity coefficients of reactions H + O2 + H2 O ↔ HO2 + H2 O (R35) and H + CH3 (+M) ↔ CH4 (+M) (R52) increases with increased H2 concentration. The combined effect of CO2 and H2 on the rate of consumption of CO via R99 for all tested fuels having CH4 :CO2 from 1:1 to 4:1 was predicted computationally. The rate of consumption of CO was least for CH4 :CO2 = 1:1 and the peak value of the rate of consumption increases with decreasing CO2 concentration irrespective of H2 concentration in the fuel.